Facilitating Indonesian EFL pre-service teachers - Syahria, Nukmatus; Khabib, Samsul; Kunhimohamed, Balkeese Binti V (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
Research on the Kampus Mengajar program has revealed challenges for teachers, particularly in advancing their professional development. However, other studies suggest that the program holds the potential for a significant positive impact on teacher professional growth. This study explores how the Kampus Mengajar program contributes to the professional development of pre-service teachers, focusing on their perspectives and experiences. This narrative case study involved four pre-service teachers from a private university in Surabaya, Indonesia. Data were collected through reflective notes and semi-structured interviews. Data were analyzed using thematic analysis deductively to explore prominent themes. The findings indicate that the Kampus Mengajar program supports pre-service teachers' professionalism by enhancing their pedagogical knowledge, teaching skills, and problem-solving abilities. Participants appreciated the program for boosting their self-efficacy and helping them master the 4C skills: critical thinking, creativity, communication, and collaboration. This study underscores the value of teaching practicums in fostering future teachers' professionalism. Despite some challenges in the program's implementation, the empirical evidence suggests that the Kampus Mengajar program should be continued.